Collecting duct of Bellini renal carcinoma with psoas muscle recurrence: A case report and review of literature - Chua, Michael Erlano; Olondriz, Karen; Maniwa, Michael; Mendoza, Jonathan; Castillo, Josefino (Canadian Urological Association Journal, 2014)
Collecting duct carcinoma (CDC) is a rare type of renal carcinoma with an aggressive course and poor treatment response. Up to date, there are only few reports of CDC, which may be due to unrecognized or unfamiliarity of its features and characteristics. We report a case of CDC in a 63-year-old male who initially presented with localized disease, and developed psoas muscle metastasis 15 months after partial nephrectomy with good surgical margins. No guidelines currently exist for the management of CDC; however, aggressiveness of the disease warrants close surveillance and consideration of adjuvant therapy even in patients with localized tumours. We postulate that CDC in its localized stage can be managed by partial nephrectomy, while preserving renal function; however, it is also important to consider a good oncologic outcome by administering adjuvant therapy, such as chemotherapy, and targeted therapy for a better prognostic outcome.